What advice do general practitioners give to people living with obesity to lose weight? a qualitative content analysis of recorded interactions - Tremblett, M; Poon, A; Aveyard, P; Albury, C (Oxford University Press, 2022)
Background: Guidelines recommend general practitioners (GPs) take every opportunity to talk to people living with obesity about their weight, and evidence shows even very brief advice is associated with weight loss. However, little is known about what GPs say when giving brief behavioural advice, and if it reflects evidence-based recommendations for people living with obesity. To understand what behavioural advice GPs give, we categorised the content and delivery of GPs’ advice during brief interventions.